Pentingnya penanaman karakter di era digital - Al Zakky, Muhammad Zidan (Maliki Interdisciplinary Journal, 2024)
The digital era has brought major changes to the world of education, including in terms of character development. On the one hand, digital technology can be a powerful tool for instilling moral and ethical values ​​in students. On the other hand, technology can also carry risks that can harm students' character development. Character education in the digital era must focus on forming a strong and responsible young generation. Students should be encouraged to develop the values ​​of responsibility, honesty, empathy and justice. These values ​​can help the younger generation to become individuals who are wise, intelligent and have integrity in utilizing digital technology. Character cultivation requires cooperation from various parties, such as educators, parents and the community. Educators must be role models for students and demonstrate positive behavior. Parents must give love and attention to children. Digital technology can be used to expand the scope and effectiveness of character formation, such as through social media, webinars and online seminars. Even though there are various obstacles, such as negative content, changes in social interaction patterns, consumerist culture, lack of parental role, and poor role models from community leaders, character education in the digital era is still important and must continue to be carried out. With cooperation from various parties, the young generation can be instilled with noble character and ready to face various challenges and opportunities in the future.